Performance Comparison of Handover Rerouting Schemes in Wireless ATM Networks - Abu-Khadra, Fawwaz Y. M. (1999)
The major issue of the integration of wireless and wired ATM is the support of user mobility. In effect, many technical challenges have been posed due to mobility support. One of the most important challenges is the rerouting of active connections of mobile user during handover. The rerouting of connections must exhibit low handover latency, limit the handover delay or disruption time, maintain efficient routes and minimise the impact on existing infrastructure. To date, two dominant approaches have been proposed to support mobility into fixed ATM network. The first is the mobility enhanced switches approach and the second is the separate network-elements specific to mobility approach. The first approach implies updating the existing ATM switches with mobile specific features. The mobility functions in the second approach are entrusted to a control station attached to the ATM switch as is implemented by the Magic WAND projects. In this thesis, we investigate how mobility can be supported using both approaches. To demonstrate the effectiveness of the above approaches, we compare the performance by analytically derived formulate for their hand over latency, hand over delay, buffer size, and bandwidth requirements. The formulate were derived for both backward and forward hand overs using a number of potential rerouting schemes proposed for wireless ATM network. The results show that the mobility enhanced switches approach has slightly better performance than the separate network elements approach. The results also show that backward handover has better performance than forward handover in terms of the handover delay and buffer requirement. Finally, the results show that the Anchor Switch rerouting scheme is the best among other rerouting schemes proposed for wireless ATM.